Assessment of geotechnical properties of bacteria treated sandy soil - Lim, Jonathan Han Yi. (2009)
Liquefaction has induced catastrophic damages to our infrastructure in the past years, and efforts have been made to make structures less to prone to liquefaction. One way is to design liquefaction resistant houses, and the other way is to do soil improvement.Soil improvement can be done in many ways; either by densification or by increasing the soil’s drainage capacity. Means of densifying the soil include vibrofloatation, dynamic compaction, casting stone columns in-situ, installing compaction piles and grouting. Increasing the drainage capacity can be done by installing drains in the soil by use of synthetic material. As most of these conventional soil improvement techniques are expensive, or potentially harmful to the environment. In the case of chemical grouts, it was analysed the feasibility of microbial technology as a soil improvement technique. One promising approach is biocementation. Biocementation seeks to enhance the stiffness of the soil properties via microbial activity or products. As the scale of geotechnical construction is very large, treating the soil with bacteria could prove to be a cost effective method. Some important factors that govern the use of microorganisms include the identification of the types of bacteria, applications in situ, different environments, biosafety, optimization of microbial activity and long term stability of soil properties after treatment with bacteria. The experiments that were carried out showed that soil that is treated microbially do exhibit an increase in strength as well as a decrease in permeability. Both iron reducing bacteria and urealytic bacteria can be used to produce biological cementation within short periods of time.